A simulation of segregation in cities and its application for the analysis of price regulation - Wolfgang Wagner (European Regional Science Association (ERSA), 2004)
Social segregation in cities takes place where different household groups exist and when, according to Schelling, their location choice either minimizes the number of differing households in their neighbourhood or maximizes their own group. In this contribution an evolutionary simulation based on a monocentric city model with externalities among households is used to discuss the spatial segregation patterns of four groups. The resulting complex spatial patterns can be shown as graphic animations. They can be applied as initial situation for the analysis of the effects a price regulation has on segregation. JEL classification: D62, R14, R31, R52 Keywords: simulation, segregation, monocentric city, price regulation
Keywords: D62; R14; R31; R52; 330; simulation; segregation; monocentric city; price regulation